Chronic Exposure to Arsenic in Drinking Water Causes Alterations in Locomotor Activity and Decreases Striatal mRNA for the D2 Dopamine Receptor in CD1 Male Mice - Claudia Leticia Moreno Ávila; Jorge H. Limón-Pacheco; Magda Giordano; Verónica M. Rodríguez (Journal of Toxicology)
Arsenic exposure has been associated with sensory, motor, memory, and learning alterations in humans and alterations in locomotor activity, behavioral tasks, and neurotransmitters systems in rodents. In this study, CD1 mice were exposed to 0.5 or 5.0 mg As/L of drinking water for 6 months. Locomotor activity, aggression, interspecific behavior and physical appearance, monoamines levels, and expression of the messenger for dopamine receptors D1 and D2 were assessed. Arsenic exposure produced hypoactivity at six months and other behaviors such as rearing and on-wall rearing and barbering showed both increases and decreases. No alterations on aggressive behavior or monoamines levels in striatum or frontal cortex were observed. A significant decrease in the expression of mRNA for D2 receptors was found in striatum of mice exposed to 5.0 mg As/L. This study provides evidence for the use of dopamine receptor D2 as potential target of arsenic toxicity in the dopaminergic system.